Automating psycholinguistic statistics computation: procura palavras - Machado, João F. (2010)
This article describes psycholinguistic lexical databases available in various languages, including English, Spanish and Portuguese. These lexical databases are important for re- searchers in Psycholinguistics and other related areas, providing a pool of experimental materials and allowing for an efﬁcient process of selection of these experimental materials. The process of gathering statistics is slow, resulting in a small pool of materials in the short-term. The need to ﬁnd an alternative method to gather limited or yet unavailable statistics for a speciﬁc language led us to consider gathering statistics from other languages and to compute their triangulation. Our aim was to automatize the computation of statistics such as Fa- miliarity, Imageability, Age of Acquisition and Written Word Frequency for that speciﬁc language. We will describe the process of preparing this data and tri- angulating and comparing statistics for some languages in an at- tempt of ﬁnding a relationship between them. The results were analysed considering correlations between each statistic in each pair of languages and by computing the mean of absolute dif- ferences between each language’s values.